Genomic loss in environmental and isogenic morphotype isolates of Burkholderia pseudomallei is associated with intracellular survival and plaque-forming efficiency. - Natnaree Saiprom; Tanes Sangsri; Sarunporn Tandhavanant; Sineenart Sengyee; Rungnapa Phunpang; Anucha Preechanukul; Uriwan Surin; Apichai Tuanyok; Ganjana Lertmemongkolchai; Wasun Chantratita; T Eoin West; Narisara Chantratita (Public Library of Science (PLoS), 2020)
Background Burkholderia pseudomallei is an environmental bacterium that causes melioidosis. A facultative intracellular pathogen, B. pseudomallei can induce multinucleated giant cells (MNGCs) leading to plaque formation in vitro. B. pseudomallei can switch colony morphotypes under stress conditions. In addition, different isolates have been reported to have varying virulence in vivo, but genomic evolution and the relationship with plaque formation is poorly understood. Methodology/principle findings To gain insights into genetic underpinnings of virulence of B. pseudomallei, we screened plaque formation of 52 clinical isolates and 11 environmental isolates as well as 4 isogenic morphotype isolates of B. pseudomallei strains K96243 (types II and III) and 153 (types II and III) from Thailand in A549 and HeLa cells. All isolates except one environmental strain (A4) and K96243 morphotype II were able to induce plaque formation in both cell lines. Intracellular growth assay and confocal microscopy analyses demonstrated that the two plaque-forming-defective isolates were also impaired in intracellular replication, actin polymerization and MNGC formation in infected cells. Whole genome sequencing analysis and PCR revealed that both isolates had a large genomic loss on the same region in chromosome 2, which included Bim cluster, T3SS-3 and T6SS-5 genes. Conclusions/significance Our plaque screening and genomic studies revealed evidence of impairment in plaque formation in environmental isolates of B. pseudomallei that is associated with large genomic loss of genes important for intracellular multiplication and MNGC formation. These findings suggest that the genomic and phenotypic differences of environmental isolates may be associated with clinical infection.